Film po adaptacji powieści: narracja Wojny polsko-ruskiej pod flagą biało-czerwoną - Wacław Osadnik (Postscriptum Polonistyczne)
In the theoretical part of the article the author discusses the notion of cultural equivalency from the perspective of the polysystem theory, proposed by Gideon Toury, Jose Lambert and Itamar EvenZohar. The theory assumes that literature is a formal dynamic functional system, and that the translation of a literary work of art rejects the requirement of adequacy for the sake of acceptability.